MAHMUD YUNUS DAN KONTRIBUSINYA DALAM PERKEMBANGAN STUDI HADIS DAN ILMU HADIS DI INDONESIA - Andi Sahputra Harahap (STAI Tuanku Tambusai, 2019)
Hadith study and hadith science which develop in Indonesia today are inseparable from important figures. Among them is Mahmud Yunus. This article is historically-philosophical which will examine the thoughts and contributions of Mahmud Yunus in the historical development of Hadith study and hadith science in Indonesia. This research uses library research method and historical-philosophical approach in which it is obtained some conclusions; Mahmud Yunus did not have any special thoughts about the hadith or hadith science, he composed a book or hadith book as a teaching material in a madrasah or school with a very simple model. Likewise in the field of ulum al-hadis, he only explains the basics briefly by quoting from earlier scholars’ books without discussing in more depth as it is in the Musthalah al-Hadith Science. Mahmud is more concerned with methods of teaching than the material.